ANALISIS PENGELOLAHAN DATA ABSENSI DAN PENGGAJIAN BERBASIS MICROSOFT EXCEL PADA PT. KRIYA ALAM INDONESIA - Evi Voish Elvido Maria; Varrel Voish Elvido Wypa (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2026)
This research investigates the management of attendance and payroll data at PT. Kriya Alam Indonesia, aiming to improve financial reporting accuracy and efficiency through a Microsoft Excel-based system. The current manual attendance system leads to data inaccuracies, manipulation risks, and payroll errors, impacting employee satisfaction and operational efficiency. The study identifies problems within the existing system, analyzes the impact of inaccurate data on financial reports, and proposes Excel-based solutions for effective data management. The anticipated outcome is an enhanced Excel system that improves accuracy, efficiency, and timely financial reporting for the management team, supporting informed decision-making. This report offers practical insights for PT. Kriya Alam Indonesia to optimize data management practices and contribute to a broader understanding of effective data management in similar SMEs, highlighting the potential of Excel for improving financial reporting. This study also aims to improve the company's resources through the use of an enhanced system.